Subarachnoid haemorrhage and cerebral vasculopathy in a child with sickle cell anaemia. (21st October 2014) - Inusa, Baba; Casale, Maddalena; Booth, Caroline; Lucas, Sebastian
Abstract : Stroke in sickle cell anaemia (SCA) is either infarctive or haemorrhagic in nature. In childhood, over 75% of strokes in SCA are infarctive. We present an adolescent with SCA who developed hypertension at the age of 13, and was treated with lisinopril. Sixteen months later she was found in cardiorespiratory arrest and died on arrival in hospital. The last transcranial Doppler scan performed 6 months before her death and a brain MRI were reported normal. The autopsy discovered massive subarachnoid haemorrhage in association with vascular damage in the circle of Willis arteries. The case highlights a cause of haemorrhagic stroke, the first reported association between hypertension, SCA and a histopathologically proven cerebral vasculopathy. The difficulties in the management of haemorrhagic stroke and the poor outcome in SCA are discussed.